Rani Gaidinliu: legendary freedom fighter from the North East - Kamei, Som (New Delhi: Niyogi Books, 2022)
Rani Gaidinliu was a legendary freedom fighter from north east India. As a teenager, she bravely stood up to the might of the British empire, and fought for justice and freedom from colonial repression of her community, the Zeliangrong Nagas
Keywords: Rani Gaidinliu; freedom fighter; North East